2021
DOI: 10.3389/fphys.2021.705838
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Macrophages in Kidney Fibrosis

Abstract: The phenotypic heterogeneity and functional diversity of macrophages confer on them complexed roles in the development and progression of kidney diseases. After kidney injury, bone marrow-derived monocytes are rapidly recruited to the glomerulus and tubulointerstitium. They are activated and differentiated on site into pro-inflammatory M1 macrophages, which initiate Th1-type adaptive immune responses and damage normal tissues. In contrast, anti-inflammatory M2 macrophages induce Th2-type immune responses, secr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
66
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(85 citation statements)
references
References 121 publications
2
66
0
Order By: Relevance
“…Previous results on the role of the innate immunity system in post-infarction myocardial regeneration in humans and animals [8,10,11] and its place in cardiorenal interactions in animals provided the rationale for studying this issue [6,7,12,13]. Involvement of monocytes/macrophages in both the inflammatory and regenerative phases of post-infarction myocardial remodeling has already been confirmed by the presence of their prolonged CD68+, CD163+, CD206+ and stabilin-1+ macrophage infiltration in both IA and non-IA of the myocardium in patients who experienced a fatal MI [10].…”
Section: Discussionmentioning
confidence: 99%
“…Previous results on the role of the innate immunity system in post-infarction myocardial regeneration in humans and animals [8,10,11] and its place in cardiorenal interactions in animals provided the rationale for studying this issue [6,7,12,13]. Involvement of monocytes/macrophages in both the inflammatory and regenerative phases of post-infarction myocardial remodeling has already been confirmed by the presence of their prolonged CD68+, CD163+, CD206+ and stabilin-1+ macrophage infiltration in both IA and non-IA of the myocardium in patients who experienced a fatal MI [10].…”
Section: Discussionmentioning
confidence: 99%
“…Unexpectedly, macrophage and monocyte accumulation was reduced by chemokine treatment, whereas it was aggravated by blockade of CCL9, although without significant impact on the ratio of M2 to M1 macrophages. Monocytes and pro-inflammatory M1 macrophages are well-known to contribute to ongoing kidney inflammation and damage [ 27 ]. Moreover, although M2 macrophages can mediate anti-inflammatory effects upon acute kidney injury, they contribute to CKD by promoting kidney fibrosis and increasingly accumulate in the injured kidney during CKD development [ 27 , 28 , 29 , 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…αSMA is a commonly used biomarker for myofibroblast, which plays a critical role in tissue fibrosis. 23,24 We found that the number of F4/ 80 + αSMA + MMT cells was decreased after GW2580 treatment when compared with the vehicle group (Figures 4B and 5). Our results suggested that GW2580 treatment could attenuate bladder fibrosis by partially inhibiting F4/80 + αSMA + MMT cells.…”
mentioning
confidence: 85%